Hepatic interferon regulatory factor 8 expression suppresses hepatocellular carcinoma progression and enhances the response to anti–programmed cell death protein‐1 therapy. Issue 6 (24th January 2022) - Wu, Hongxi; Li, Yan; Shi, Guangjiang; Du, Shijia; Wang, Xiaobin; Ye, Wanli; Zhang, Zixuan; Chu, Ya; Ma, Shuqian; Wang, Dajia; Li, Yuan; Chen, Zhen; et al.
Abstract: Background and Aims: Therapeutic blockade of the programmed cell death protein‐1 (PD‐1) immune checkpoint pathways has resulted in significant reactivation of T cell–mediated antitumor immunity and is a promising clinical anticancer treatment modality in several tumor types, but the durable response rate remains relatively low (15%–20%) in most patients with HCC for unknown reasons. Evidence reveals that the interferon signaling pathway plays a critical role in modulating the efficacy and sensitivity of anti–PD‐1 therapy against multiple tumor types, but the mechanisms are unclear. Approach and Results: Using Kaplan‐Meier survival analysis based on HCC databases, we found that deceased expression of interferon regulatory factor (IRF) 8 in HCC, among all the nine IRF members that regulate interferon signals, was associated with poor prognosis of patients with HCC. Moreover, gene set enrichment analysis identified the interferon‐gamma and PD‐1 signaling signatures as the top suppressed pathways in patients with IRF8‐low HCC. Contrarily, overexpression of IRF8 in HCC cells significantly enhanced antitumor effects in immune‐competent mice, modulating infiltration of tumor‐associated macrophages (TAMs) and T cell exhaustion in tumor microenvironment. We further demonstrated that IRF8 regulated recruitment of TAMs by inhibiting the expression of chemokine (C‐C motif) ligand 20 (CCL20). Mechanically, IRF8‐mediated repression of c‐fos transcription resulted in decreased expression of CCL20, rather than directly bound to CCL20 promoter region. Importantly, adeno‐associated virus 8–mediated hepatic IRF8 rescue significantly suppressed HCC progression and enhanced the response to anti–PD‐1 therapy. Conclusions: This work identified IRF8 as an important prognostic biomarker in patients with HCC that predicted the response and sensitivity to anti–PD‐1 therapy and uncovered it as a therapeutic target for enhancing the efficacy of immune therapy.